2016
DOI: 10.1093/jnci/djw224
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uba6-Specific-E2 (USE1) With Lung Tumorigenesis

Abstract: USE1 proteins are frequently overexpressed in lung cancer, and missense mutations in USE1 prolong the half-life of the protein, promoting tumor formation. Our findings reveal novel roles for USE1 in lung cancer and the possible use of USE1 as a novel biomarker and therapeutic target for lung cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…For instance, FAT10 has demonstrated protumorigenic functions in hepatic and gastrointestinal malignancies (Lee et al, 2003;Yuan et al, 2014). Similarly, the UBA6-specific E2 enzyme UBA6-specific E2 conjugating enzyme 1 (USE1) is overexpressed in a subset of patients with lung cancer and promotes tumor growth, migration, and invasiveness (Kim et al, 2017). In contrast, UBA6 is inversely related to invasiveness in a subset of breast cancer in which it suppresses mammary carcinogenesis of breast cancer cells by inhibiting epithelial-mesenchymal transition (Liu et al, 2017b).…”
Section: Ubiquitin-like Modifier-activating Enzymementioning
confidence: 99%
“…For instance, FAT10 has demonstrated protumorigenic functions in hepatic and gastrointestinal malignancies (Lee et al, 2003;Yuan et al, 2014). Similarly, the UBA6-specific E2 enzyme UBA6-specific E2 conjugating enzyme 1 (USE1) is overexpressed in a subset of patients with lung cancer and promotes tumor growth, migration, and invasiveness (Kim et al, 2017). In contrast, UBA6 is inversely related to invasiveness in a subset of breast cancer in which it suppresses mammary carcinogenesis of breast cancer cells by inhibiting epithelial-mesenchymal transition (Liu et al, 2017b).…”
Section: Ubiquitin-like Modifier-activating Enzymementioning
confidence: 99%
“…Kim et al found that 92.5% of tumor-normal-paired samples derived from 106 cancer patients showed a significantly upregulated USE1 expression, while the mRNA level of USE1 remained unchanged [112]. The unchanged mRNA level suggests an increased translation or decreased degradation of the USE1 protein in cancer tissues [113].…”
Section: Use1mentioning
confidence: 99%
“…A relevant study investigated UBA6-specific E2 conjugating enzyme 1 (USE1). The results showed that mutations in USE1 resulted in lung tumorigenesis by prolonging the half-life of the protein ( 52 ). We believe that USE1-associated UBA6 might be a participator in the prognosis of LUAD patients.…”
Section: Discussionmentioning
confidence: 99%